Violencia simbólica en el barrio: exploración conceptual desde las manifestaciones de violencia simbólica en los barrios de la ciudad de Medellín, Colombia, entre 2009 y 2019 - Felipe Dávila, Luis (Derecho penal y criminología, 2023)
The present text intends to conceptually explore the category of symbolic violence in the neighborhood, taking its manifestations in the city of Medellín between 2009 and 2019 as a reference. To achieve this, we compile a state of the art, oriented from a historical-hermeneutic macro mold, where forty texts that directly related the category of symbolic violence within the neighborhood context were compiled. The information was then processed by the qualitative analysis software Atlas TI. The material reviewed deals with various issues, for example, the presence of illegal armed groups, the construction of masculinities, latent affective relationships at the neighborhood level and the dynamics of popular culture, among others. One of the results obtained is that Pierre Bourdieu’s concept of “symbolic violence” has been used in different contexts and for multiple issues, leading to a view of the concept as kind of academic wild card. In conclusion, it was possible to identify that the concept in question has become detached from its original conception (at least in the case of Medellín and its closest region), but in turn, it has become a useful analytical tool to understand different types of injustices or social violations.